Synthesis, characterization, photophysical and photochemical properties of 7-oxy-3-methyl-4-phenylcoumarin-substituted indium phthalocyanines - (:unkn) unknown (ELSEVIER SCIENCE SA, 2011)
The synthesis of tetra- and octa-(7-oxy-3-methyl-4-phenylcoumarin)-substituted indium(III) phthalocyanine complexes obtained from 3-nitrophthalonitrile, 4-nitrophthalonitrile and 4,5-dichlorophthalonitrile substituted with 7-oxy-3-methyl-4-phenylcoumarin are described for the first time in this study. The new compounds have been characterized by elemental analysis, IR, H-1 NMR, electronic spectroscopy and mass spectra. The photophysical and photochemical properties of the compounds are also studied in dimethylformamide (DMF). The effects of the number of the substitution and the position on the photophysical and photochemical parameters of the substituted indium(III) phthalocyanine complexes are also reported. Photophysical and photochemical properties of phthalocyanine complexes are very useful for photodynamic therapy (PDT) of cancer applications. In particular, high singlet-oxygen quantum yields are very important for Type II mechanisms. These complexes have good singlet-oxygen quantum yields and show potential as Type II photosensitizers. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Fluorescence; Phthalocyanine; Quantum yield; Singlet oxygen; Indium; SUBSTITUTED GALLIUM; QUANTUM YIELDS; NAPHTHALOCYANINES; DERIVATIVES; BEHAVIOR